2021
DOI: 10.3389/fphar.2021.613805
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Medical Cannabis Treatment is Associated With Quality of Life Improvement and Reduction of Analgesic Medication Consumption in Chronic Pain Patients

Abstract: Introduction: Chronic non-cancer pain (CNCP) is one of the most prevalent indications for medical cannabis (MC) treatment globally. In this study, we investigated CNCP parameters in patients during prolonged MC treatment, and assessed the interrelation between CNCP parameters and the chemical composition of MC chemovar used.Methods: A cross-sectional questionnaire-based study was performed in one-month intervals for the duration of six months. Subjects were adult patients licensed for MC treatment who also rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Although 86% reported on at least 1 AE, the most frequent AEs were gastrointestinal (70%), central nervous system (60%), psychological (45%), ophthalmic (34%), musculoskeletal (31%), and cardiovascular (10%) and were also stable during the follow-up. 2 However, we did not investigate whether these considerable rates of AEs could be explained by sex differences. Thus, in the current study, using the same database, we attempted to examine whether there are sex differences in MC-related rates of AEs and whether such differences are associated with the chemical composition of the MC treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Although 86% reported on at least 1 AE, the most frequent AEs were gastrointestinal (70%), central nervous system (60%), psychological (45%), ophthalmic (34%), musculoskeletal (31%), and cardiovascular (10%) and were also stable during the follow-up. 2 However, we did not investigate whether these considerable rates of AEs could be explained by sex differences. Thus, in the current study, using the same database, we attempted to examine whether there are sex differences in MC-related rates of AEs and whether such differences are associated with the chemical composition of the MC treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Similar long-term safety was previously demonstrated in cancer patients ( 67 ). It is plausible that THC dose increase in the current study was not associated with elevation of AEs rates because it is unrelated or that patients that started consuming MC products with higher THC concentration are those less susceptible to its effects, as was demonstrated in a study on the sex differences of MC related AEs ( 68 ). Nonetheless, we found that THC monthly dose increased significantly in the 6 months of MC treatment from a Median (IQR) of 2,000 mg (1,000–3,000) to 3,000 mg (2,000–4,000).…”
Section: Discussionmentioning
confidence: 70%
“…Patients in the sample were on average 64 ( 49 68 ) years old and the majority (59% n = 192) were females. Previous exposure to cannabis was reported by 20% ( n = 65) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 17 Hence, administration of MC with conventional administration routes may result in overdosing or AEs even after a prolonged duration of treatment. 3 …”
Section: Discussionmentioning
confidence: 99%